Novel cryotherapy in non–muscle‐invasive bladder cancer. Issue 3 (7th December 2022) - Ho, Matthew D.; Modi, Parth K.
Abstract : In this editorial, the recently published trial examining endoscopic balloon cryoablation after resection of non–muscle‐invasive bladder cancers is discussed. Several issues with the control group, design, and inclusion criteria that limit the application of these data to current urologic practice are identified.